PERAN NAZHIR DALAM MENGELOLA HASIL WAKAF UANG PADA BADAN WAKAF INDONESIA JAWA TIMUR - Risca Putri Prasinanda; Tika Widiastuti (Universitas Airlangga, 2019)
This research aims at determining the competence of Nazhir on its efforts to manage cash waqf to empower productive society. Analysis technic done on this study is descriptive qualitative with case study method where this research is done by doing direct observation, taking documentation and all the data provided, and interviewing all the related parties to this matter, so that the data gained are able to answer all the research questions. The result of this research show that Indonesian Waqf Board has done its duty in accordance with the Regulation no 41 year 2004 to manage and develop cash waqf properly, it needs human resources which are reliable, professional, knowledgeable in economics, perseverance, and having strong commitment. Therefore, cash waqf institution has a really strategic role on creating a productive waqf in Indonesia, therefore a training is needed to the waqf managers (nazhirs), a continuous socialization from academicians, ulamas, sharia economics practicians, either from seminar, training, preaches, or mass media articles.Keywords: Baitul Mal Wat Tamwil, Financing Fund, Prosperity, SME, Maqasid shariah